PROFILE OF SINONASAL TUMOR PATIENT IN ADAM MALIK GENERAL HOSPITAL 2016-2018 - Ulya, Ulfatul; Ashri Yudhistira; Rambe, Andrina Y.M; Yetty Machrina (Sumatera Medical Journal, 2020)
Abstract. Sinonasal tumor is a neoplasm that arises from nasal and paranasal sinus tissue. It is rarely found, only <3% of all malignancy in head and neck, and 1% of all malignancy in the body. Although it is rarely found, it can cause serious complication in adult. Unspecific sign and symptoms of sinonasal tumor often make the patients ignore the disease. It leads to the diagnosis of this disease becomes late and the patients come to the doctor in advanced stage. This research was conducted to know about the profile of sinonasal tumor patients in H. Adam Malik Medan Hospital on 2016-2018. The study was a descriptive study with retrospective approach. The data used are secondary data taken from medical records. The data were analyzed using a statistical application programs. Sinonasal tumor patients in RSUP HAM Medan are 158 patients, where 95 patients met the inclusion criteria, consisting of 24 benign tumors (25,3%) and 71 malignant tumors (74,7%). The majority of patients are male (71,6%), and the highest age group in in 51-60 years old (31,6%). The main complaints felt by the patients were nasal symptoms (64,2%), the location of tumors mostly found in nasal cavity (50,5%), the most histopathological type is NKSCC (43,2%), the most occupation is self-employment (26%), and the treatment of the patients are surgery (29,5%). Keyword: Sinonasal Tumor, Profile, Sinonasal Cancer